Fake heroines and the falsification of history in Zimbabwe 1980 - 2009 - Goredema, Dorothy; Chigora, Percyslage (Academic Journals, 2014)
The ideology of femocracy is so entrenched in Zimbabwean politics that it has become a tradition. It started as a tendency during the liberation struggle of making room and integrating a few women into politics. After independence, it developed into a habit of promoting the same women who had been exposed during the liberation struggle into political offices. Finally, at independence it became a tradition whereby the state confers heroine status to the very women who had held position during the war. However, one feature that stands glaring at the national heroes’ acre is that the heroines who were lay, are all related to men in political positions in both current ruling party and the state. This paper will demonstrate that most Zimbabwean heroines are forgotten. It also proves that even at death the patriarchal nature of Zimbabwean politics manifests itself when one considers that the number of male heroes vis-à-vis the heroines who lay at the acre. Finally the paper will show how femocracy as an ideology has led to the falsification and misrepresentation of historical facts all in an attempt to promote nationalist history.